Binuclear O2 activation and hydrogen transfer mechanism for aerobic oxidation of alcohols. Issue 7 (4th March 2020) - Hu, Zhiyun; Ge, Hongyu; Yang, Xinzheng
Abstract : Density functional theory calculations reveal a binuclear O2 activation and hydrogen transfer mechanism with spin-crossovers for aerobic oxidation of alcohols. Abstract : A density functional theory study of the aerobic oxidation of 1-phenylethanol into acetophenone catalysed by phenanthroline copper (phenCu) complexes reveals a binuclear O2 activation and hydrogen transfer mechanism with multiple spin-crossover steps. When di- tert -butyl azodicarboxylate (DBAD) exists, it acts as a stoichiometric oxidant and forms DBADH2 through successive transfers of the proton and hydride from 1-phenylethanol to DBAD in one transition state with a free energy barrier of 21.8 kcal mol −1 . After the consumption of DBAD, DBADH2 acts as a co-catalyst assisting O2 activation and acetophenone formation through binuclear transition states for the cleavages of O–O and C–H bonds with a total free energy barrier of 24.6 kcal mol −1 . Without the presence of DBAD or DBADH2, the total free energy barrier for the aerobic oxidation of 1-phenylethanol with the participation of two phenCu complexes is 26.1 kcal mol −1 . In all the above three situations, the rate-determining step is the activation of the C–H bond in 1-phenylethanol. The formation of HOO˙ radical and the breaking of the O–O bond in hydrogen peroxide for the formation of a Cu(ii )-hydroxyl dimer are also key steps in the reaction and need the participation of two phenCu complexes.